Numerical Simulation on Flow Field of Oilfield Three-Phase Separator - Yong-tu Liang; Sheng-qiu Zhao; Xia-xue Jiang; Xian-qi Jia; Wang Li (Journal of Applied Mathematics)
The conventional measurement method can no longer guarantee the accuracy requirement after the oilfield development entering high water cut stage, due to the water content and gas phase in the flow. In order to overcome the impact of measurement deviation the oilfield production management, the flow field of three-phase separator is studied numerically in this paper using Fluent 6.3.26. Taking into consideration the production situation of PetroChina Huabei Oilfield and the characteristics of three-phase separator, the effect of internal flow status as well as other factors such as varying flow rate, gas fraction, and water content on the separation efficiency is analyzed. The results show that the separation efficiencies under all operation conditions are larger than 95%, which satisfy the accuracy requirement and also provide the theoretical foundation for the application of three-phase separators at oilfields.